S129 Neutrophil function and advancing age: the effects of Simvastatin in health and during pneumonia. (2nd December 2011) - Sapey, E; Greenwood, H; Hazeldine, J; Walton, G; Thickett, D; Lord, J M; Stockley, R A
Abstract : Background: Age is associated with a decline in immunity, including neutrophil function. This may partially explain the worsening clinical outcomes seen following pneumonia in the elderly. Statins may improve outcomes from pneumonia although it is unknown whether they influence neutrophil function at conventional therapeutic concentrations. This is crucial, as statins may be beneficial adjuvants during infections. Methods: We studied the effect of 5 ng/ml Simvastatin (equivalent to 80 mg orally) on key neutrophil functions: speed and accuracy of migration using time-lapse imaging (μm/min), Neutrophil Extracellular Trap formation using cell-impermeable DNA-binding dye (in AFU) and generation of reactive oxygen species (ROS, in RLU). Results: We studied 70 healthy subjects (aged 20–90 years, 10 in each decennial) and 6 young (<35 years) and 6 older (>65 years) patients during an admission with pneumonia. All studied neutrophil functions declined with age (eg, neutrophil chemotaxis, r =−0.7, p<0.001). Specifically, average neutrophil chemotaxis for subjects >65 yrs was 0.72 μm/min (SD ± 0.28, p<0.001) slower than subjects <35. These neutrophils produced less NETS (average difference =−1725AFU±283, p=0.007) and peak ROS (average difference −117RLU±31; p=0.04). Neutrophils from young patients with pneumonia displayed an up-regulation of function that was not seen in older pneumonia patients. There were no age-associated differences in the surface expression of chemo-attractant receptors, but there appears to be differential intracellular signalling with reduced expression of adhesion molecules. Incubating neutrophils from older subjects with Simvastatin improved all functions back to that seen in young subjects (chemotactic speed + 0.92 μm/min ±0.27, p=0.001: NET + 1386AFU±273, p=0.04: ROS +223RLU±39, p=0.005). Similar improvements were seen with neutrophils from older subjects with pneumonia. This was a dose-dependent phenomenon; not seen at higher concentrations of Simvastatin. Conclusion: With age, there is a global deterioration in neutrophil function and no up-regulation when pneumonia is present, which may partially explain the age-associated mortality. Simvastatin up-regulates neutrophil function in the elderly, even during pneumonia. This up-regulation may explain the beneficial effects seen clinically. In vivo studies are warranted, to determine if simvastatin should be utilised during episodes of acute infection.